A synopsis of the subgenus Centris (Hemisiella) Moure, 1945 (Hymenoptera: Apidae: Centridini) in Colombia, with description of a new species - Vivallo, Felipe; Vélez, Danny (Zootaxa, 2016)
A synopsis of the species of Centris subgenus Hemisiella Moure in Colombia is presented. The species included are Centris dichrootricha (Moure), C. facialis Mocsáry, C. merrillae Cockerell, C. tarsata Smith, C. trigonoides Lepeletier and C. vittata Lepeletier. In addition, C. nebulosa new species from northwestern Colombia is described, as well as the male of C. merrillae. Diagnoses for both sexes, occurrence records, and an identification key for the seven species of the subgenus that occur in the country are provided.